Les organisations intermédiaires locales, un acteur clé dans la mise en œuvre et les résultats du programme de paiements pour services environnementaux au Costa Rica - Jean-François Le Coq; Fernando Saenz Segura (Développement Durable et Territoires)
Although its performance has been discussed, the national program of payment for environmental services of Costa Rica (PPES) is considered as a successful experience regarding forest recovery. This paper aims at characterizing the specific contribution of local intermediaries’ organizations to the implementation and results of PPES. We show that these organizations are diverse and contribute to PPES environmental and social performances through their capacity to provide a large of set of services to forest owners which facilitate their access to the program and valorize the land use it supported but not by their ability to reduce the costs of access to the program beard by the PPES beneficiaries.